A behavioral economics‐based telehealth intervention to improve aspirin adherence following hospitalization for acute coronary syndrome. Issue 5 (31st March 2020) - Riegel, Barbara; Stephens‐Shields, Alisa; Jaskowiak‐Barr, Anne; Daus, Marguerite; Kimmel, Stephen E.
Abstract: Purpose: A significant number of patients with acute coronary syndrome (ACS) are nonadherent to aspirin after hospital discharge, with an associated increased risk of subsequent cardiovascular events. The purpose of this pilot study was to test the efficacy of a telehealth intervention based on behavioral economics to improve aspirin adherence following hospitalization for ACS. Methods: We enrolled 130 participants (c¯X = 58 ± 10.7 years of age, 38% female, 45% black) from two hospitals. Patients were eligible if they owned a smartphone and were admitted to the hospital for ACS, prescribed aspirin at discharge, and responsible for administering their own medications. Consenting participants were randomized to the intervention or usual care group. The intervention group was eligible to receive up to 50 per month if they took their medicine daily, with 2 per day deducted if a dose was missed. All participants received an electronic monitoring (EM) pill bottle containing a 90‐day supply of aspirin, which was used to measure adherence calculated as the proportion of prescribed drug taken using the EM device. Based on the skewness in the adherence distribution, quantile regression was used to evaluate the effect of the intervention on median adherence over time. Results: After 90 days, adherence fell in the control group but remained high in the intervention group (median adherence 81% vs 90%, P = .18). Rehospitalization was higher in the control group (24% vs 13%, P = .17). Conclusion: A loss aversion behavioral economics‐based telehealth intervention is a promising approach to improving aspirin adherence following hospitalization for ACS.